Business plan on plus size clothing online store / Emyza Aisah Atang - Atang, Emyza Aisah (2018)
The interest in the plus-size clothing has been gaining popularity due to the increase level of obesity issues, which reports a large mass of people from across the globe that automatically demanded the need for a plus-size market. Plus size market has seen an incredible increasing growth through internet or e-commerce sales channel. This study was conducted to analysing and identify the factors that contributed to online shopping motivations of plus size fashion online consumers. Both primary and secondary sources were used to gather insights about the industry and customer behaviour local and international. An online survey was created to gather customer insights in the Malaysia, with more focus in Kuching, Sarawak. Other sources were from official information published about the industry by government, individuals and industry competitors. Overall, this project has been conducted using the acquired knowledge from the market research and reliable literature. This has helped in defining the business mission; marketing and organizational plans and the financial plans which will subsequently be further developed. Recommendations are finally provided for the entrepreneurs and start-ups on how to be sustainable and utilize all the available opportunities provided by the plus size clothing retailer industry especially in Malaysia.